Estimation of stiffness derivative of an ogive for specific heat ratio 1.666 - Shabana, Aysha; Monis, Renita Sharon; Crasta, Asha; Khan, Sher Afghan (The Mattingley Publishing Co., Inc, 2019)
This paper focusses attention on studying the effect of the flow medium on the aerodynamic characteristics of the ogive at significant inertia levels. Accordingly, the hypersonic similitude is used to find analytical expression to evaluate the pressure dissemination on the exterior of the ogive and hence, finally to get the stiffness derivatives for Mach quantities from the Mach number M = 5 to 15, and the stream ricochet directions in the range from 100 to 250. This study considers two values of the λ = 5, and 10 are for the ogival shape of the nose. The γ value considered is 1.666. Using this value of the specific heat ratio the expression for rigidityderived for an ogive through the assumption that the gas is in-viscid and ideal, the indication is semi-steady, and the front noseapproach of the ogive is to such an extent that the inertia level behindhand the tremor M2 after the shock M2 ≥ 2.5 . The consequencesdesignate that with the rise in the Mach number since M = 5 to M = 15, Initially the magnitude of the stiffness derivative and later with superfluousrise in the Mach (M), it befitsself-regulating of inertia level and Mach independence principle has revisited. When the λ = 10, there is a swing of the midpoint of force towards the leading edge.